Memotivasi Masyarakat Pesisir Pulau Setokok Kota Batam Untuk Membentuk Koperasi Nelayan - Suhardi, Suhardi; Kurniawan, Ade (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
From the initial survey and the joint interview, Mr. Amigus Arif as the chairman of RT 02 RW 02 on Setokok Island, stated that the lives of the people were trapped with loans with loan sharks. This is due to the lack of knowledge about how to manage money well. For this reason, Community Service was funded by the DPRM Community Partnership Program (PKM) with the aim of motivating and encouraging the coastal communities of Setokok Island in Batam City to form fishing cooperatives there as a solution. The target of the service was the coastal community of Setokok Island, Bulang Sub-District, Batam City, Riau Islands. The method used is observation to the location of partners conducting interviews, discussions, and conducting counseling and coaching with the community there. Topics and materials provided in counseling and guidance, namely: Introduction of cooperatives, types of cooperatives and their benefits, and social media marketing. This service level is in addition to increasing people's knowledge about cooperatives, they can also form fishing cooperatives later.